Proportional accumulation of yolk proteins derived from multiple vitellogenins is precisely regulated during vitellogenesis in striped bass (Morone saxatilis). Issue 6 (20th March 2014) - Williams, Valerie N.; Reading, Benjamin J.; Amano, Haruna; Hiramatsu, Naoshi; Schilling, Justin; Salger, Scott A.; Islam Williams, Taufika; Gross, Kevin; Sullivan, Craig V.
ABSTRACT We quantified three vitellogenins (VtgAa, VtgAb, VtgC) or their derived yolk proteins (YPs) in the liver, plasma, and ovary during pre‐vitellogenic (PreVG), mid‐vitellogenic (MVG), and late‐vitellogenic (LVG) oocyte growth and during post‐vitellogenesis (PostVG) in the striped bass (Morone saxatilis) using label‐free quantitative mass spectrometry (MS). Western blotting of the samples using antisera raised against gray mullet (Mugil cephalus) lipovitellins derived from VtgAa, VtgAb, and VtgC confirmed the MS results. Semi‐quantitative reverse transcription polymerase chain reaction (RT‐PCR) revealed liver as the primary site of expression for all three Vtgs, with extra‐hepatic transcription weakly detected in ovary, foregut, adipose tissue, and brain. Quantitative real‐time RT‐PCR confirmed vtgAb to be primarily expressed in liver and VtgAb proteins were predominant in liver and plasma from MVG to PostVG. However, the primary period of deposition into oocytes of VtgAb occurred up until MVG, whereas VtgAa was primarily deposited from MVG to LVG. The VtgC was gradually taken up by oocytes throughout vitellogenesis and was detected at trace levels in plasma. The ratio of yolk proteins derived from VtgAa, VtgAb, VtgC (YPAa/YPAb/YPC) in PostVG ovary is 1.4:1.4:1, which differs from ratios previously reported for other fish species in that YPC comprises a greater proportion of the egg yolk. Our results indicate that proportional accumulation of multiple Vtgs in the yolk may depend both on the precise rates of their hepatic secretion and specific uptake by oocytes. Furthermore, composition of the Vtg‐derived yolk may vary among Acanthomorph fishes, perhaps reflecting their different early life histories and reproductive strategies. J. Exp. Zool. 321A: 301–315, 2014. © 2014 Wiley Periodicals, Inc.